Rapidly progressive puberty in a patient with mosaic Turner syndrome a case report and literature review - Liang, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2017)
Objective: To explore the clinical characteristics of diagnosis and treatment in patients with Turner syndrome and rapidly progressive puberty. Method: A rare case of rapidly progressive puberty in Turner syndrome with a mosaic karyotype of 45, X/46, X, del(X)(p21)(80%/20%)was diagnosed at Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology in January. 2015. Clinical characteristics and the related literature were reviewed. Original papers on precocious puberty or rapidly progressive puberty in Turner syndrome, published until Apr. 2016 were retrieved at PubMed and CNKI databases by the use of the key words "Turner syndrome" , "precocious puberty" and "rapidly progressive puberty" . Result: The patient was born at term with birth weight of 2 450 g and was diagnosed with SGA at 3 years of age for the first evaluating of growth and development. Then recombined human growth hormone (rhGH )was given at 4 years of age due to short stature (height<3 percentile) and low growth velocity(<5.0 cm/year) as well. However, rhGH treatment was discontinued after 9 months because of economic burdens. Breast development was noted at 9 years and 3 months. The patient was followed up at 3 months intervals. Physical examination revealed a Tanner stage Ⅲ breast development at 10.33 years , the bone age was 11.6 years. Then, gonadotropin-releasing hormone analogs treatment was added to slow pubertal progression and to preserve maximum adult height. The growth rate decreased with therapy from 7.5 cm/year to 4.4 cm/year. The patient was reevaluated, and the chromosome analysis of peripheral blood revealed a mosaic karyotype 45, X/46, X, del(X)(p21)(80%/ 20%). To date, only 10 cases have been reported in the literature. Six of them showing mosaic TS, three karyotypes with structural abnormality of short arm of X chromosome, one with the karyotype 45, X. Conclusion: It is the first time that rapidly progressive puberty in a 45, X/46, X, del(X)(p21) mosaic Turner syndrome is reported. Although short stature and ovarian dysgenesis are common in TS, precocious puberty may occur in TS, which is liable to cause delayed diagnosis and misdiagnosis. Careful examination is recommended for patients with unusual growth pattern, even though girls have normal height in accord with standard growth curve or spontaneous puberty. Evaluation for TS and subsequent investigation should be prompted